Heritability and familiality of neurological soft signs: evidence from healthy twins, patients with schizophrenia and non-psychotic first-degree relatives. Issue 1 (8th September 2015) - Xu, T.; Wang, Y.; Li, Z.; Huang, J.; Lui, S. S. Y.; Tan, S.-P.; Yu, X.; Cheung, E. F. C.; He, M.-G.; Ott, J.; Gur, R. E.; Gur, R. C.; et al.
Abstract : Background: Neurological soft signs (NSS) have long been considered potential endophenotypes for schizophrenia. However, few studies have investigated the heritability and familiality of NSS. The present study examined the heritability and familiality of NSS in healthy twins and patient–relative pairs. Method: The abridged version of the Cambridge Neurological Inventory was administered to 267 pairs of monozygotic twins, 124 pairs of dizygotic twins, and 75 pairs of patients with schizophrenia and their non-psychotic first-degree relatives. Results: NSS were found to have moderate but significant heritability in the healthy twin sample. Moreover, patients with schizophrenia correlated closely with their first-degree relatives on NSS. Conclusions: Taken together, the findings provide evidence on the heritability and familiality of NSS in the Han Chinese population.